[Letter to Premier Couillard re: English Schools / Lettre au premier ministre Couillard concernant les écoles anglaises] - Quebec Community Groups Network (QCGN) (2015)

QFHSA Fall Conference 2015 - Quebec Federation of Home and School Associations (QFHSA) (2015)

English School Boards Election Systems Study Panel 2015 - Election Systems Study Panel (ESSP) (Quebec Community Groups Network (QCGN), 2015)
The Election Systems Study Panel (ESSP), launched in June of 2015 and sponsored by the Quebec English School Boards Association (QESBA), the English Parents’ Committee Association (EPCA), the Québec Community Groups Network (QCGN) and the Québec Federation of Home and School Associations (QFHSA), is an independent volunteer Panel consisting of five members of the English Minority Community (EMC). Chaired by the Honourable Marlene Jennings, former Member of Parliament, other Panel members include former Assistant Deputy Minister from the Ministry of Education Leo La France, Executive Director of Townshippers’ Association Rachel Hunting1, President of QFHSA Brian Rock, and Vice‐President of EPCA Rhonda Boucher. The Panel’s mandate included the review of numerous election systems as well as the current system of universal suffrage for the selection of Commissioner and Chairs; consultations with English Minority organizations and individuals with expertise on the various options; a review of past elections; and making recommendations for the four sponsor organizations to present to the Québec government. The Panel investigated all system options through the prism of Official Language Minority Community (OLMC) Constitutional Rights
Keywords: Official Language Minority Community (OLMC)

A Brief on School Board Elections Systems - The Rights and Education Committee of the Quebec Federation of Home and School Associations (Quebec Federation of Home and School Associations (QFHSA), 2015)
Due to the importance of elected English school boards to the English-speaking community, in 2014 the Québec Federation of Home and School Associations Inc. (QFHSA) decided to get involved in promoting school board elections. The Rights, Education and Resolutions Committee (RER) was mandated to produce a Special Bulletin on School Board Elections, which would include contributions from the Québec English School Board Association (QESBA), the Québec Community Groups Network (QCGN), out-going School Board Commissioners as well as a QFHSA Brief on School Board Elections Systems message from our own president, Lawrence DePoe. Included in the bulletin would be information on returning officers and how to get on the right voters list. The intention was to provide as much information as possible to parents to boost voter turnout at the polls. This information would be of benefit to Home and School parents and the general public. Forty thousand (40,000) copies of the Special Bulletin were printed and distributed to all English public schools in Quebec, with assistance from QESBA through their internal mail system. Consensus at the QFHSA Board of Directors’ as well as within the QFHSA Rights Education and Resolutions and Editorial Committees’, was that the future of school boards in Québec was at stake, and this justified the special effort.
Keywords: Official Language Minority Community (OLMC)

71st Annual General Meeting & Conference - Quebec Federation of Home and School Associations (QFHSA) (2015)

Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (2015)

Resolution 2015-01 : Diversity and Inclusion - Quebec Federation of Home and School Associations (QFHSA) (2015)

Resolution 2015-02: History of Residential Schools - Quebec Federation of Home and School Associations (QFHSA) (2015)

Résolution 2015-02 : L'histoire des Pensionnats - Quebec Federation of Home and School Associations (QFHSA) (2015)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2015)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2015)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2015)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2015)

School and School Yard Maintenance : Resolution 2015/03 - Quebec Federation of Home and School Associations (QFHSA) (2015)